Conservation and valorization of Italian potato biodiversity through genotype-by-sequencing (GBS) - Martina, M.; Natale, R.; Vergnano, E.; Milani, A. M.; Biricolti, S.; Andrenelli, L.; Portis, E. (Frontiers in Plant Science, 2025)
IntroductionTraditional crop varieties are vital for conserving agrobiodiversity, ensuring food security, and preserving cultural heritage. However, Italian potato (Solanum tuberosum) landraces, shaped by centuries of farmer selection and adaptation to diverse agroecological conditions, are increasingly threatened by genetic erosion and agricultural homogenization.MethodsTo support their conservation, we collected 61 accessions from 22 traditional Italian landraces, documented their traditional culinary uses, and evaluated tuber skin and pulp color. Virus presence was assessed and sanitation protocols were applied. Genetic diversity was analyzed using genotyping-by-sequencing (GBS), and comparisons were made with a global reference panel of 106 genotypes.ResultsGBS data revealed marked genetic differentiation among the Italian landraces, with three main genetic clusters showing internal structure and minimal overlap with commercial varieties. The Italian germplasm was clearly distinct from worldwide accessions, underlining its unique genetic identity.DiscussionThe observed diversity highlights the potential of traditional landraces as a valuable resource for breeding programs aimed at enhancing resilience to climate change. This integrated approach fosters both agrobiodiversity conservation and the socio-economic development of marginal areas, offering a model for safeguarding traditional crop diversity worldwide.